Hodnocení finanční situace podniku a návrhy na její zlepšení - Dostálová, Šárka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Bakalářská práce se zabývá finančním hodnocením situace vybrané společnosti pomocí vybraných metod finanční analýzy v letech 2012 – 2015. Na základě výstupů, které finanční analýza poskytla, je vydefinována současná situace a jsou následně navrhnuta řešení. Návrhy představují doporučení, které by měla vést ke zlepšení finanční situace společnosti v budoucích letech.

This bachelor thesis deals with a financial situation evaluation of a selected company using specific financial analysis methods in the years 2012 – 2015. Based on the outcome of the financial analysis, the current situation is described and several proposals in regards to the situation are made. The proposals include recommendations that should result in an improvement of the company's financial situation in the future.
Evaluation of Financial Situation in Firm and Proposals to its Improvement
Keywords: finanční analýza; finanční situace; metody; finanční výkazy; SWOT; financial analysis; financial situation; methods; financial statemenst; SWOT